PENYULUHAN PENDIDIKAN INKLUSIF DALAM QS. AL-HUJURAT AYAT 10-13 SEBAGAI SOLUSI EKSKLUSIFISME AJARAN DI KALANGAN MAHASISWA STAI FATAHILLAH SERPONG TANGERANG SELATAN BANTEN - Kerwaanto Kerwaanto; Liana Masruroh; Zakaria Husin Lubis; Abdelaziz Abbaci; Ahmad Zulki; Mutholib Mutholib (MADANI Abdimas : Jurnal Penelitian dan Pengabdian Masyarakat, 2025)
The rise of anarchist activity and terrorism has recently become a central issue in Indonesian national life. This happens because people's understanding of a multiethnic and multireligious society is increasingly becoming more ambiguous. One solution is to introduce inclusive (open) education in schools. The concept of education is included in the teachings of the Islamic holy book, the Koran. It was explained that the world community was created as a multi-ethnic nation so that they could know and respect each other. The author uses library research methods to analyze the concept of inclusive education at QS. Verses 10-13 of Surah al-Khujrat. In this case the author uses this as the basis for indoctrination in Islamic education in schools. Inclusive education is a conscious effort to build society through structured and continuous involvement with an open, dynamic and rational learning system. To achieve peace and social prosperity, an open attitude is needed, starting with the desire to get to know each other and respect differences without distinguishing between certain groups. This is achieved by introducing open and inclusive education in schools